Bantuan tangan kasih (Keberpihakan pemerintah daerah dalam upaya stabilisasi ketahanan sosial dan ekonomi masyarakat di Kota Sorong): Helping hands of love (Local government alignment to stabilize social and economic resilience of communities in Sorong City ) - Ana Lestari Anna; Salmawati; Awal Fikri (JOURNAL OF GOVERNMENT SCIENCE, 2024)
This study aims to determine and describe the form of government alignments in efforts to stabilize the social and economic resilience of the community in the implementation of Bantuan Tangan Kasih in Sorong City in 2021 to 2022. This research uses a descriptive qualitative approach. Location research was conducted in Sorong City, precisely at the Sorong City Manpower Office as the authorized agency in the implementation of Bantuan Tangan Kasih. Data collection techniques were carried out using observation, interview and documentation methods. The data analysis technique uses the Huberman and Miles interactive analysis model, namely, data reduction, data display, conclusion drawing. Bantuan Tangan Kasih is a social assistance program that focuses on people who are not validated as beneficiaries of social assistance from the government, for example, BPNT, BLT, PKH or other similar social assistance. The principle of no left behind is a form of government partiality to people who are economically disadvantaged but not validated as recipients of government assistance or complementary social assistance. The alignment aspect of the Sorong City Government is clearly visible after the implementation process which includes data collection of prospective recipients, distribution and reports on the results of the implementation of the Bantuan Tangan Kasih Assistance has been completed. From 2020 to 2022, the Hand of Love Assistance in Sorong City has been implemented well and received a positive response from the community. The form of government partiality can be interpreted through the process of creativity/innovation, implementation, commitment.